2023
DOI: 10.1097/qco.0000000000000905
|View full text |Cite
|
Sign up to set email alerts
|

Skin and soft tissue infections due to rapidly growing mycobacteria

Abstract: Purpose of reviewThe aim of this article is to review skin and soft tissue infections due to rapidly growing mycobacteria (RGM), with a particular focus on recently published literature (2021–2022).Recent findingsRGM are increasingly reported as a cause of skin and soft tissue infections, both in the community setting and as a cause of nosocomial outbreaks. Recent advances in molecular methods have expanded the number of species of RGM and resulted in increased diagnosis. New treatment options are under evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…the skin via a wound or inhalation of aerosols with contaminated soil or water (11,33). Moreover, recent studies demonstrated the occurrence of person-to-person transmission between CF patients in a healthcare setting, raising concerns regarding the ability of the pathogen to spread and the impact it will have on public health (13,18).…”
Section: I2 Mycobacterium Abscessus An Emerging Pathogenmentioning
confidence: 99%
See 4 more Smart Citations
“…the skin via a wound or inhalation of aerosols with contaminated soil or water (11,33). Moreover, recent studies demonstrated the occurrence of person-to-person transmission between CF patients in a healthcare setting, raising concerns regarding the ability of the pathogen to spread and the impact it will have on public health (13,18).…”
Section: I2 Mycobacterium Abscessus An Emerging Pathogenmentioning
confidence: 99%
“…Skin and soft tissue disease include the infection of the skin, cartilage, tendons and fat layers, and is generally a localized disease with symptoms such as redness and swelling (33,39). Unlike MABC-PD, skin and soft tissue disease can be found in healthy individuals without preexisting conditions, mostly in a healthcare settings (28,40).…”
Section: I22 Clinical Presentationmentioning
confidence: 99%
See 3 more Smart Citations